The bioethical and human rights challenges surrounding the HIV testing of women in South Africa and other sub-Saharan African countries - O'Grady, Mary Josephine (My University, 2016)
The purpose of this thesis is to explore the current HIV testing protocols, especially provider-initiated counselling and testing, otherwise known as ‘routine testing,’ under implementation in sub-Saharan African countries and examine whether and how they transgress bioethical and philosophical principles and the human rights of women in the current context of the highly stigmatised HIV epidemic. The research method employed is mainly a literature review partly based on my 20 years of experience working on HIV testing programmes and programmatic evaluations in sub-Saharan African countries, from which earlier background papers and this thesis topic grew. Included in this primarily moral examination are the historical philosophical and present bioethical principles of autonomy, beneficence, justice, and non-maleficence, the philosophical right to self-preservation, and relevant human rights principles and recent examples of human rights infringements related to the HV testing, in particular, the routine testing of women in sub-Saharan African countries. A conclusion is reached that where HIV testing is practiced in sub-Saharan African countries, and anywhere for that matter, without alignment with the bioethical principles of respect for autonomy, justice, beneficence, and non-maleficence, and without protecting the human rights of individuals testing for HIV, including the provision of pre- and post-test counselling, implementing the informed consent process, maintaining the confidentiality of test results, and making referrals to other services available to all individuals who test negative or positive, as well as making antiretroviral therapy (ART) available to anyone who tests HIV-positive, such testing is unethical. Thus I posit that without the aforementioned conditions, the routine testing for HIV of all individuals presenting to a clinic for healthcare—and the routine testing of all pregnant women for HIV—amidst the highly stigmatised HIV epidemic in sub-Saharan Africa is unethical.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment for the requirements for the degree of Doctor of Philosophy Johannesburg, 2015